2000
DOI: 10.1002/1097-4636(20000905)51:3<299::aid-jbm2>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of fracture repair in rats with streptozotocin-induced diabetes by a single injection of biodegradable microcapsules containing a bone formation stimulant, TAK-778

Abstract: The feasibility of using microcapsules containing a b o n e f o r m a t i o n s t i m u l a n t , ( 2 R , 4 S ) -( − ) -N -( 4diethoxyphosphorylmethylphenyl)-1,2,4,5-tetrahydro-4methyl-7,8-methylenedioxy-5-oxo-3-benzothiepin-2carboxamide (TAK-778) to enhance fracture repair was assessed in rats with streptozotocin-induced diabetes. The release profile of the microcapsules was designed to mimic a dosing regimen of multiple injections of TAK-778 solution. The solution was injected locally every third day from da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
11
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
4
11
0
Order By: Relevance
“…The recovery of microspheres was shown to be 50-70% for all preparations. For the mean particle sizes of the microspheres ( Table 2), all of the microspheres constructed from PLA and PLGA polymers were in the range of approximately 10-50 m, which is considered to be an adequate size (Hoshino et al, 2000). For the microspheres constructed from the PLA-PEG polymers, the mean particle sizes of microspheres constructed from PLAPEG9604H, PLAPEG9604L, PLAPEG8812, and PLAPEG8515H with a PEG proportion of between 4 and 15% were in the range of approximately 30-45 m. However, when the proportion of the PEG component exceeded 20%, it became technically difficult to prepare these microspheres.…”
Section: Resultssupporting
confidence: 72%
“…The recovery of microspheres was shown to be 50-70% for all preparations. For the mean particle sizes of the microspheres ( Table 2), all of the microspheres constructed from PLA and PLGA polymers were in the range of approximately 10-50 m, which is considered to be an adequate size (Hoshino et al, 2000). For the microspheres constructed from the PLA-PEG polymers, the mean particle sizes of microspheres constructed from PLAPEG9604H, PLAPEG9604L, PLAPEG8812, and PLAPEG8515H with a PEG proportion of between 4 and 15% were in the range of approximately 30-45 m. However, when the proportion of the PEG component exceeded 20%, it became technically difficult to prepare these microspheres.…”
Section: Resultssupporting
confidence: 72%
“…These studies include the use of lowintensity pulsed ultrasound (US), biodegradable microcapsules containing bone formation stimulant (TAK-778), recombinant human bFGF, local delivery of insulin, and the percutaneous injection of platelet-rich plasma (PRP) [24,[50][51][52][53]. US normalized the diabetes-related impairment in fracture callus strength [52]; however, US did not affect cellular proliferation in the early diabetic fracture callus.…”
Section: Diabetic Fracture Healing Adjunctsmentioning
confidence: 99%
“…The effect of US in a diabetic fracture healing model does not appear to be mediated through the normalization of cell number but possibly through increased matrix production. Hoshino and colleagues [53] reported locally delivered microcapsules of TAK-778-enhanced fracture repair in streptozotocin-induced diabetic rats. TAK-778 increased the bending strength of diabetic bone at 4 weeks and 8 weeks.…”
Section: Diabetic Fracture Healing Adjunctsmentioning
confidence: 99%
“…8 To evaluate the in vivo osteogenic potential of TAK-778, it was developed a sustained release microcapsules consisted of a biodegradable polymer, poly (dl-lactic/glycolic) acid, and TAK-778, which allow the drug release for 4 weeks after the injection. 6 Using this release system, TAK-778 has induced bone regeneration and stimulated fracture healing. 9,10 In addition, TAK-778 enhances new bone formation on hydroxyapatite and bioactive glass ceramics implanted into rabbit tibiae.…”
mentioning
confidence: 95%
“…In vitro studies have shown that TAK-778 increases both alkaline phosphatase activity in rat bone marrow cell culture and the action of bone morphogenetic protein in mouse osteoblastic cell line MC3T3-E1. 4 6 Recently, we showed that TAK-778 enhances osteoblast differentiation in human bone marrow cell culture in a dose-dependent way. 7 Also, it was observed that TAK-778 maintains its effect on osteoblast differentiation in the presence of titanium.…”
mentioning
confidence: 99%